2024
DOI: 10.11591/eei.v13i1.6317
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the performance of YOLOv5, YOLOv6, and YOLOv7 in road defect detection and classification: a comparative study

Najiha ‘Izzaty Mohd Yusof,
Ali Sophian,
Hasan Firdaus Mohd Zaki
et al.

Abstract: Road defect inspection is a crucial task in maintaining a good transportation infrastructure as road surface distress can impact user’s comfortability, reduce the lifetime of vehicles’ parts, and cause road casualties. In recent years, machine learning has been adapted widely in various fields, including object detection, thanks to its superior performance and the availability of high computing power which is generally needed for its model training. Many works have reported using machine-learning-based object … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The experimental results showed that as the proportion of injected noise increased, the performance of the YOLO algorithm gradually declined, especially when the noise ratio reached 100%, at which point performance significantly decreased, most objects could not be detected, and the detected object labels were also wrong. Mohd et al [39] evaluated and compared the performance of YOLOv5, YOLOv6, and YOLOv7 models in road defect detection and classification. The evaluation metrics used included the model's training time, mAP@0.5 (mean average precision), accuracy, and inference speed.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results showed that as the proportion of injected noise increased, the performance of the YOLO algorithm gradually declined, especially when the noise ratio reached 100%, at which point performance significantly decreased, most objects could not be detected, and the detected object labels were also wrong. Mohd et al [39] evaluated and compared the performance of YOLOv5, YOLOv6, and YOLOv7 models in road defect detection and classification. The evaluation metrics used included the model's training time, mAP@0.5 (mean average precision), accuracy, and inference speed.…”
Section: Introductionmentioning
confidence: 99%